2017
DOI: 10.3389/fpsyg.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal-Parietal White Matter Volumes in Healthy Elderlies Are Decreased in Proportion to the Degree of Cardiovascular Risk and Related to Inhibitory Control Deficits

Abstract: Cardiovascular risk (CVR) factors may be associated with poor cognitive functioning in elderlies and impairments in brain structure. Using MRI and voxel-based morphometry (VBM), we assessed regional white matter (WM) volumes in a population-based sample of individuals aged 65–75 years (n = 156), subdivided in three CVR subgroups using the Framingham Risk Score. Cognition was assessed using the Short Cognitive Performance Test. In high-risk subjects, we detected significantly reduced WM volume in the right juxt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Finally, although some studies find associations between BMI and white matter abnormalities, there were no significant associations in our analyses. Causes of white matter abnormalities include vasculopathy, demyelination, and gliosis, but the most common cause associated with aging and cerebrovascular disease is ischemic pathogenesis, or small cerebral vessel disease (Fennema-Notestine et al, 2016;Santos, P.P. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although some studies find associations between BMI and white matter abnormalities, there were no significant associations in our analyses. Causes of white matter abnormalities include vasculopathy, demyelination, and gliosis, but the most common cause associated with aging and cerebrovascular disease is ischemic pathogenesis, or small cerebral vessel disease (Fennema-Notestine et al, 2016;Santos, P.P. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al analyzed data from a large cohort of older adults ( n = 394) and showed that higher absolute cardiovascular risk was associated with smaller volume in CGM and SGM, but not in CWM ( 9 ). Santos et al ( 36 ) conducted voxel-wise morphometric MRI study of older adults ( n = 156) and reported that, compared to the low and moderate cardiovascular risk groups, the high cardiovascular risk group showed smaller white matter volumes in the prefrontal-parietal region. Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients with coronary heart disease or heart failure experience depression much more often than the general population. 2 In addition, there is evidence that cardiovascular risk factors may favour the development of cognitive decline and dementia. 3…”
Section: Ageing Is Inevitable and Increases Vulnerabilitymentioning
confidence: 99%
“…[ 2 ] In addition, there is evidence that cardiovascular risk factors may favour the development of cognitive decline and dementia. [ 3 ]…”
Section: Ageing Is Inevitable and Increases Vulnerabilitymentioning
confidence: 99%